Dickkopf-1 Is a Biomarker for Systemic Lupus Erythematosus and Active Lupus Nephritis - Jing Xue; Jiali Yang; Lijuan Yang; Shaolan Zhou; Chen Ji; Xuemei Wang; Nan Yu; Xiaoming Liu; Shuhong Chi (Journal of Immunology Research)
An early diagnosis of lupus nephritis (LN) has an important clinical implication in guiding treatments of systemic lupus erythematosus (SLE) in clinical settings. In this study, the concentrations of Wnt-3A, Frizzled-8 (FZD-8), and Dickkopf-1 (DKK-1) of Wnt signaling, as well as their diagnostic values for accessing LN, were evaluated by ELISA in sera and urine of 111 SLE patients (31 with LN and 80 without LN) and 70 healthy cohorts. Significantly more abundances of DKK-1 protein were determined in both of sera and urine of SLE patients compared to healthy cohorts (p<0.0001); in particular the serum DKK-1 concentration was even higher in LN-SLE patients relative to non-LN SLE subjects (p<0.0001). Intriguingly, concentrations of above examined proteins in SLE patients showed no correlation between serum and urine. Moreover, a combination of DKK-1 with anti-dsDNA and/or levels of complement C3 and C4 could not increase the specificity and/or sensitivity for identification of patients with LN diseases, but both ROC curve and multiple-factor nonconditional logistic regression analysis showed that serum DKK-1 was considered better positive biomarker for identification of LN in SLE patients. These results imply that serum and/or urine DKK-1 may be a valuable and independent biomarker for identification of SLE patients with LN.